INCOMPATIBLE ELEMENT-RICH FLUIDS RELEASED BY ANTIGORITE BREAKDOWN IN DEEPLY SUBDUCTED MANTLE - Scambelluri M.; Bottazzi P.; Trommsdorff V.; Vannucci R.; Hermann J.; Gomez-Pugnaire M.T.; Lopez-Sanchez Vizcano V. (My University, 2001)
We present first trace element analyses of the fluid produced during breakdown of antigorite serpentine, a major dehydration reaction occurring at depth within subducting oceanic plates. Microinclusions filled with crystals+ aqueous liquid are disseminated within olivine and orthopyroxene grown at pressures and temperatures beyond the stability field of antigorite. Despite hydrogen loss and significant major element changes that have affected the analyzed inclusions, their trace element composition still reflects characteristics of the subduction fluid released during serpentinite dehydration. The fluid is enriched in incompatible elements indicating either (1) interaction with fluids derived from crustal slab components, or (2) dehydration of altered (serpentinized) oceanic mantle previously enriched in incompatible elements. Several features of the analyzed fluid+mineral inclusions (high Pb/Th, Pb/U and Pb/Ce) are in agreement with available experimental work, as well as with the geochemical signatures of most arc lavas and of several ocean island basalt mantle sources. The trace element patterns of the fluid+mineral inclusions do not display relative enrichment in large ion lithophile elements compared to high field strength elements, thus suggesting that the latter elements may become soluble in natural subduction fluids.
Keywords: SUBDUCTION; ANTIGORITE; FLUID INCLUSIONS; TRACE ELEMENTS